Amperometric Sniffer for Volatile Amines Based on Paper‐Supported Room Temperature Ionic Liquids Enabling Rapid Assessment of Fish Spoilage. Issue 9 (26th August 2014) - Toniolo, Rosanna; Dossi, Nicolò; Svigely, Rossella; Susmel, Sabina; Casella, Innocenzo G.; Bontempelli, Gino
Abstract A gas sensors based on a room temperature ionic liquid (RTIL) supported on paper is proposed as amperometric sniffer for monitoring volatile amines (VAs) released from fish samples, in order to gain indication of their state of turning spoiled. It was used as a paper electrochemical detector (PED) for a flow injection system in which controlled headspace volumes in equilibrium with ice‐stored fish samples were directly injected. The performance of this RTIL‐PED sensor was preliminarily tested on synthetic samples of trimethylamine (TMA), dimethylamine (DMA), methylamine (MA) and ammonia (i.e. the main species responsible for the typical flavor of spoiled fish), thus verifying that only TMA, DMA and MA can be detected because NH3 oxidation occurred beyond the solvent discharge. This notwithstanding, detection of the sole TMA, DMA and MA as a whole turned out to be well suited for the rapid assessment of fish spoilage, since during storage the release enhancement for these amines is largely predominant over that of NH3. Repeatable (8 % RSD) sharp peaks were detected for all amines above over a wide range (5–1000 nmol) and a detection limit of a little more than 3 nmol was inferred for a signal‐to‐noise ratio of 3. This approach was applied to the detection of VAs released from real fish samples (sardines), in parallel to the determination of their total volatile basic nitrogen (TVBN), which is a conventional indicator frequently adopted for the chemical quality assessment of fish. A substantially satisfactory agreement was found by comparing the data achieved by these two approaches.